Creation of a High‐fidelity, Low‐cost Pediatric Skull Fracture Ultrasound Phantom. (1st August 2015) - Soucy, Zachary P.; Mills, Lisa; Rose, John S.; Kelley, Kenneth; Ramirez, Francisco; Kuppermann, Nathan
Abstract : Over the past decade, point‐of‐care ultrasound has become a common tool used for both procedures and diagnosis. Developing high‐fidelity phantoms is critical for training in new and novel point‐of‐care ultrasound applications. Detecting skull fractures on ultrasound imaging in the younger‐than‐2‐year‐old patient is an emerging area of point‐of‐care ultrasound research. Identifying a skull fracture on ultrasound imaging in this age group requires knowledge of the appearance and location of sutures to distinguish them from fractures. There are currently no commercially available pediatric skull fracture models. We outline a novel approach to building a cost‐effective, simple, high‐fidelity pediatric skull fracture phantom to meet a unique training requirement.